The Effect of Prevailing Wage Law Repeals and Enactments on Injuries and Disabilities in the Construction Industry. (October 2019) - Li, Zhi; Zorigtbaatar, Chimedlkham; Pleités, Gabriel; Fenn, Ari; Philips, Peter
State prevailing wage law repeals have been shown to lower wages and benefits—including benefits providing safety training and associated with worker retention in construction. This study tests whether prevailing wage repeals affect construction injury rates and/or the prevalence of disabilities among construction workers. Controlling for time trends in injuries and disabilities, differences between construction industry subsectors, the business cycle, and time-invariant differences between states, we find that repealing state prevailing wage laws increase construction injury rates across various types of injuries from 11.6% to 13.1% as the seriousness of injuries increases. Disabilities increase by 7.5% to 8.2% depending on the model specification. Conjoining an analysis of the effects of prevailing wage law repeals on injury rates with disability rates in construction provides alternative measures of the effects of prevailing wage laws on construction workplace safety, which addresses a well-known problem of underreporting construction injuries.